A Comparison of Concurrent Validity and Divergent Validity Happiness Scale of PERMA Theory - หันทะยุง, จุฑาวรรณ; พานทอง, กนก (JOURNAL OF SOUTHERN TECHNOLOGY, 2019)
This research aimed to compare concurrent validity of Thai Happiness Scale based on PERMA (Thai-PERMA) and test divergent validity. The sample group was 400 citizens in Sa Kaeo Province derived from multi-stage sampling. Research instruments consisted of happiness inventory for Thai-PERMA, Thai Mental Health Indicator, Thai Happiness Scale and BDI®-II. This study was done in two phases: 1) concurrent validity comparison by performing pair-wise comparison between two correlation coefficients and 2) divergent validity testing by analyzing Pearson’s product moment correlation coefficients. The research findings were as Follows (1) concurrent validity comparison between the correlation coefficient of 3 pairs of happiness scale as follows: 1) Thai-PERMA and Thai Happiness Scale vs. Thai-PERMA and Thai Mental Health Indicator, Z score was equal to 2.96 at the statistically significant level of .05, 2) Thai-PERMA and Thai Happiness Scale vs. Thai Mental Health Indicator and Thai Happiness Scale, Z score was equal to 3.26 at the statistically significant level of .05, and 3) Thai-PERMA and Thai Mental Health Indicator vs. Thai Mental Health Indicator and Thai Happiness Scale, Z score was equal to .57 without the statistical significance. And (2) divergent validity testing of Thai-PERMA and BDI®-II resulted in the negative correlation coefficient of -.79 at the statistically significant level of .01. It was concluded that Thai-PERMA developed by the researcher could be applied to measure Thai happiness or it could be one of happiness measurement alternatively.